Pupil size and social vigilance in rhesus macaques - Ebitz, R. Becket; Pearson, John M.; Platt, Michael L. (Frontiers in Neuroscience, 2014)
Complex natural environments favor the dynamic alignment of neural processing between goal-relevant stimuli and conflicting but biologically salient stimuli like social competitors or predators. The biological mechanisms that regulate dynamic changes in vigilance have not been fully elucidated. Arousal systems that ready the body to respond adaptively to threat may contribute to dynamic regulation of vigilance. Under conditions of constant luminance, pupil diameter provides a peripheral index of arousal state. Although pupil size varies with the processing of goal-relevant stimuli, it remains unclear whether pupil size also predicts attention to biologically salient objects and events like social competitors, whose presence interferes with current goals. Here we show that pupil size in rhesus macaques both reflects the biological salience of task-irrelevant social distractors and predicts vigilance for these stimuli. We measured pupil size in monkeys performing a visual orienting task in which distractors—monkey faces and phase-scrambled versions of the same images—could appear in a congruent, incongruent, or neutral position relative to a rewarded target. Baseline pupil size under constant illumination predicted distractor interference, consistent with the hypothesis that pupil-linked arousal mechanisms regulate task engagement and distractibility. Notably, pupil size also predicted enhanced vigilance for social distractors, suggesting that pupil-linked arousal may adjust the balance of processing resources between goal-relevant and biologically important stimuli. The magnitude of pupil constriction in response to distractors closely tracked distractor interference, saccade planning and the social relevance of distractors, endorsing the idea that the pupillary light response is modulated by attention. These findings indicate that pupil size indexes dynamic changes in attention evoked by both the social environment and arousal.